Establishing Key Facts About Restrictive Housing—A Systems-Level Descriptive Analysis of Restrictive Housing and the Implications for Theory, Research, and Policy - Cochran, Joshua C. (Crime & delinquency, 2025)
Concerns about restrictive housing are motivated in part by the assumption that as prison systems expanded and became more punitive, restrictive housing became overly routine. Limited empirical research exists, however, that quantifies its usage. The goal of this paper is twofold. First, we argue that a more detailed understanding of restrictive housing usage is required to advance theory, research, and evidence-based policy. Second, we bring data to bear on questions about the prevalence and trends in the use of the most routine forms of restrictive housing in Ohio prisons. We analyze 9 years of event history data to develop an empirical portrait of its use across the system and over time. We track how many individuals are placed and how long they are placed and we examine variation across facility characteristics. The paper concludes with a discussion focused on extending this work to investigate restrictive housing usage and impacts.